Diseño de una cara emocional para un robot humanoide - Herrera-Espinoza, Jose Carlos (Instituto Tecnológico de Costa Rica, 2016)
The following document describes the design process for an emotional face for a humanoid robot in the Autonomous Robots and Cognitive Systems (ARCOSLAB) from the University of Costa Rica. This project comes up as an opportunity to upgrade the robot appearance, and to allow the robot to interact with people. The project was divided in two main areas the study and selection of the suitable emotions for the robot and the mechanical and electrical design of the face. During the first stage emotions were studied and selected based in the scenarios where the robot will be used. In the second stage the mechanical design was made, as well as the electrical and control design to perform the movement of the actuators. Finally, a prototype was built to analyze strengths and weaknesses in the design and make some test with different people.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería en Mecatrónica, 2016.
Keywords: Robots; Emociones; Prototipo; Actuadores